Ovarian Reserve: A Critical Indicator of Female Reproductive Health - Julia Ufnal; Anna Wolff; Maria Morawska; Dominika Lewandowska; Dominika Rosińska-Lewandoska; Marcelina Szewczyk; Klaudia Kożuchowska; Dawid Pilarz; Kinga Jarosz; Szymon Gruszka (Journal of Education, Health and Sport)
Introduction: Ovarian reserve, defined as the quantity and quality of a woman’s remaining oocytes, is a critical determinant of fertility potential. The finite pool of oocytes established in utero declines progressively throughout life, which is a natural process but may result in diminished ovarian reserve (DOR) in some women. DOR can affect personal and demographic outcomes, as it is closely tied to reduced fertility potential. The global trend of delayed motherhood has further highlighted the need for accurate assessment tools and interventions to manage fertility challenges. This review aims to provide a concise overview of current knowledge on ovarian reserve, Moreover, it explores the factors affecting it to contextualize these insights within the broader challenges faced by women with diminished ovarian reserve. It also explores emerging potential interventions as well as innovative assessment tools that could enhance diagnostic accuracy.